Association between antenatal glucocorticoid exposure and the activity of the stress system, cognition, and behavior in 8‐ to 9‐year‐old children: A prospective observational study - Florian Rakers; Ekkehard Schleußner; Isabel Muth; Dirk Hoyer; Sven Rupprecht; Karin Schiecke; Tanja Groten; Michelle Dreiling; Valeska Kozik; Matthias Schwab; Heike Hoyer; Carolin Ligges (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Glucocorticoid (GC) ‐induced fetal programming of the activity of the hypothalamus–pituitary–adrenal axis (HPAA) and its associated cognitive and behavioral consequences in later life have been well characterized in several animal species. However, information on humans is scarce. In this study, we examined HPAA activity markers and associated outcomes at 8 to 9 years of age among children prenatally exposed to GC for suspected preterm birth. Our hypothesis was that antenatal exposure to the betamethasone (BM) is associated with exacerbation of HPAA activity in childhood. Material and methods Prospective observational study in 31 children whose mothers received single (n = 19) or multiple (n = 12) courses of BM for threatened preterm birth but born with normal weight appropriate for the gestational age (median 37+6 weeks of gestation) compared with 38 non‐exposed, age‐matched children. Primary end point was the activity of the HPAA in response to the Trier Social Stress Test. Secondary end points were changes in autonomic nervous system (ANS) activity, cognitive performance (IQ), attention‐deficit/hyperactivity disorder (ADHD) symptoms, and electrocortical activity (EEG). Results There was no statistically significant difference in HPAA activity markers between antenatal BM exposed and unexposed groups. ANS activity in BM‐exposed children shifted towards a higher parasympathetic tone reflected by a higher overall high‐frequency band power of heart rate variability. IQ scores were within normal limits for both groups; however, BM‐exposed children had lower IQ scores than the unexposed group. BM‐exposed group had marginally more ADHD core symptoms and increased electrocortical activity in the occipital brain region compared with controls. A monotonic dose–response relation between BM exposure and activity of the ANS and IQ was estimated in post‐hoc analyses. Conclusions Antenatal exposure to BM in the context of threatened preterm birth was not associated with changes in HPAA activity in childhood. However, BM exposure may be associated with changes in ANS activity. Antenatal GC prophylaxis is a valuable and often life‐saving therapy, but its prescription may warrant a well‐balanced risk–benefit assessment.